May capillaroscopy be a candidate tool in future algorithms for SSC-ILD: Are we looking for the holy grail? A systematic review - Smith, Vanessa; Vanhaecke, Amber; Guerra, Miguel G.; Melsens, Karin; Vandecasteele, Els; Paolino, Sabrina; Cutolo, Maurizio (Autoimmunity reviews, 2020)
To investigate whether nailfold videocapillaroscopy (NVC), an increasingly worldwide used non-invasive tool to reliably evaluate the peripheral microcirculation, may be an outcome measure in future screening algorithms for systemic sclerosis related interstitial lung disease (SSc-ILD). A systematic review to identify original research papers documenting an association between NVC and SSc-ILD was performed in 3 electronic databases according to the PRISMA guidelines. Subsequently, NVC parameters were subdivided according to the consented standardised capillaroscopic definitions of the EULAR Study Group on Microcirculation in Rheumatic Diseases / Scleroderma Clinical Trials Consortium on Capillaroscopy, into quantitative (capillary density, capillary dimension, capillary morphology and haemorrhages) and qualitative assessment (NVC pattern). The systematic search identified 310 unique search results, of which 2 cross-sectional and 1 longitudinal study were retained. In both cross-sectional studies, the presence of SSc-ILD was found to be inversely associated with capillary density (p = .008 and p = .005). The presence of a severe (active/late) NVC pattern was evaluated and associated with the presence of SSc-ILD in one of the cross-sectional studies. In the longitudinal study, incident SSc-ILD was associated with progressive capillary loss (p = .03) and the conversion to a worse (active/late) NVC pattern (p = .001/p = .003). This first systematic literature review investigating the role of NVC in SSc-ILD using standardised capillaroscopic definitions uncovered associations between NVC and (incident) SSc-ILD. If large prospective studies further corroborate and elucidate these findings, NVC might possibly be a candidate outcome measure to be integrated in screening algorithms for incident/progressive SSc-ILD. •This is the first systematic review investigating the role of NVC in SSc-ILD, using consented standardised definitions•Capillary density and (worsening to) a severe NVC pattern are associated with (incident) SSc-ILD•NVC might be integrated as a candidate outcome in future screening algorithms for incident/progressive SSc-ILD